2015
DOI: 10.1523/jneurosci.0913-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms for Acoustic Signal Detection under Strong Masking in an Insect

Abstract: Communication is fundamental for our understanding of behavior. In the acoustic modality, natural scenes for communication in humans and animals are often very noisy, decreasing the chances for signal detection and discrimination. We investigated the mechanisms enabling selective hearing under natural noisy conditions for auditory receptors and interneurons of an insect. In the studied katydid Mecopoda elongata species-specific calling songs (chirps) are strongly masked by signals of another species, both comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…Studies in Ensifera (crickets and bush‐crickets) focus on ear function and afferent sensory neurons (reviewed in Mason & Faure, 2004; Yack, 2004; Stumpner & Nowotny, 2014), central auditory processing including information coding and its relevance for intraspecific behavior and predator detection (reviewed in Gerhardt & Huber, 2002; Hedwig, 2014) and the evolution of the auditory systems (Desutter‐Grandcolas, 2003; Shaw & Lesnick, 2009; Strauß & Lakes‐Harlan, 2009; Stumpner & von Helversen, 2001). The structure and response properties of prothoracic auditory interneurons are well studied (Atkins & Pollack, ; Kostarakos & Römer, ; Rheinlaender, ; Stumpner & Molina, ; Triblehorn & Schul, ), but little is known about the prothoracic auditory network and its functional design (Molina & Stumpner, ; Pollack & Imaizumi, ; Römer et al, ; Triblehorn & Schul, ). Experimental evidence indicates that local prothoracic neurons contribute to the processing of sound direction, carrier frequency, and temporal patterns in crickets (Faulkes & Pollack, ; Hardt & Watson, ; Selverston et al, ) and bush‐crickets (Prešern et al, ; Rheinlaender, ; Römer, ; Römer et al, ; Schul, ; Stumpner, ; Stumpner & Molina, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Ensifera (crickets and bush‐crickets) focus on ear function and afferent sensory neurons (reviewed in Mason & Faure, 2004; Yack, 2004; Stumpner & Nowotny, 2014), central auditory processing including information coding and its relevance for intraspecific behavior and predator detection (reviewed in Gerhardt & Huber, 2002; Hedwig, 2014) and the evolution of the auditory systems (Desutter‐Grandcolas, 2003; Shaw & Lesnick, 2009; Strauß & Lakes‐Harlan, 2009; Stumpner & von Helversen, 2001). The structure and response properties of prothoracic auditory interneurons are well studied (Atkins & Pollack, ; Kostarakos & Römer, ; Rheinlaender, ; Stumpner & Molina, ; Triblehorn & Schul, ), but little is known about the prothoracic auditory network and its functional design (Molina & Stumpner, ; Pollack & Imaizumi, ; Römer et al, ; Triblehorn & Schul, ). Experimental evidence indicates that local prothoracic neurons contribute to the processing of sound direction, carrier frequency, and temporal patterns in crickets (Faulkes & Pollack, ; Hardt & Watson, ; Selverston et al, ) and bush‐crickets (Prešern et al, ; Rheinlaender, ; Römer, ; Römer et al, ; Schul, ; Stumpner, ; Stumpner & Molina, ).…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum in the song covers a wide frequency range, which includes both audio and ultrasonic frequencies up to 80 kHz. A frequency analysis has shown that both song motifs exhibit similar spectral compositions (Kostarakos and Römer 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, this species uses its potential for frequency analysis in the ear to detect the small spectral difference between the conspecific and a heterospecific signal to avoid strong masking. Intracellular recordings of identified interneurons revealed two mechanisms providing response selectivity to the chirp (Kostarakos and R€ omer 2015). Several identified interneurons exhibit remarkably selective responses to the chirps, even at signalto-noise ratios of -21 dB, since they are sharply tuned to 2 kHz.…”
Section: Noise Filtering Through Novelty Detectionmentioning
confidence: 96%